Analisis Visi Misi Lembaga Pendidikan: Studi Kasus MAN 1 Medan - Rangga Hasibuan; Isnaini Sapitri Br Purba; Wisnu Fadhilla; Abdul Fattah Nasution (Lembaga Pengembangan Kinerja Dosen, 2024)
This research examines how the vision and mission in the management of educational institutions, with a focus on MAN 1 Medan. The background of this research stems from the need to improve the quality of human resources in the era of rapid development of science and technology. The method used is a literature study, by collecting and analysing various current literature on the vision and mission of education. The research findings show that a clear and relevant vision serves as a strategic guide in decision-making and educational policy development. In addition, a well-defined mission helps in formulating concrete steps to achieve the vision. The study also emphasises the importance of involving all stakeholders in the vision and mission formulation process so that they can be internalised and accepted by all members of the school community. The purpose of this study is to provide a better understanding of how an effective vision and mission can improve the quality of education and produce globally competitive graduates.